THE EFFECT OF SELF-AWARENESS, SELF-CONTROL, SELF-MOTIVATION, SOCIAL AWARENESS, AND SOCIAL SKILLS ON PERFORMANCE OF MSME WOMEN ENTERPRISES - Pawestri, Pebrianti; Prasetyani, Dwi (Institut Agama Islam Negeri Kerinci, 2024)
Purpose: The research aims to measure the relationship between self-awareness, self-control, self-motivation, social awareness, and social skills and business performance of female entrepreneurs. Design/methodology/approach: The total population in this study was 248 businesses. The analysis used in this research used several PLS methods, which included several analyses, including Factor Analysis, Designing a Structural Measurement Model (Inner Model), Designing a Measurement Model (Outer Model), and Hypothesis Testing. Findings: The effect of self-awareness on the performance of MSMEs shows a coefficient value of 0.435. The effect of self-control on the performance of MSMEs shows a coefficient value of 0.054. The effect of self-motivation on the performance of MSMEs shows a coefficient value of 0.273. The effect of social awareness on the performance of MSMEs shows a coefficient value of 0.048, and the effect of social skills on the performance of MSMEs shows a coefficient value of 0.246. Research implications: This research shows that self-awareness, self-control, self-motivation, social awareness, and social skills have a positive and significant effect on MSME performance.